DESIGN PRODUCTION SCHEDULING AT PT X USING THE FLOW SHOP SCHEDULING APPROACH - Yemima Budisusanto, Nathania
PT X is a private company that operates in Bandung district with the main product being shoes, especially safety shoes, sport shoes, and security shoes. Until now, PT X has 33 types of shoes that can be divided into 2 categories based on the assembly process between upper part of the shoes and the soles which are vulcanized and cementing shoes. Vulcanized shoes are made by going through some work stations including cutting – sewing – lasting – molding – vulcanized finishing, while cementing shoes are made by going through cutting – stockfit – sewing – cementing – cementing finishing work stations. PT X applies flow shop production method and make-to-order system for their order fulfilment method. Lately, PT X often experiences delays in fulfilling customer orders since the production department fails to meet the daily production target. This is caused by PT X irrelevant scheduling method that is not in accordance with their needs which is First Come First Served (FCFS) sequencing method. Thus, this study aims to find the best scheduling method for PT X in order to minimize total makespan and minimize maximum lateness. The proposed design will consist production scheduling for PT X using 2 sequencing rules which are Shortest Processing Time (SPT) and Earliest Due Date (EDD), and also flow shop scheduling method which is Campbell Dudek Smith (CDS) algorithm. The result of the proposed scheduling method shows that minimum total makespan achieved is 32.23 days using CDS algorithm and minimum maximum lateness is 8.72 days using EDD sequencing rules, both of which are better than the result of actual scheduling method. After selecting these 2 best scheduling methods, a scheduling program was created using Microsoft Excel Macro to automate scheduling process in PT X. The improvement of PT X’s production scheduling process is expected to accelerate the fulfillment of customer orders and to minimize order fulfillment delay by PT X.